Strategizing Bangladesh’s Post-Hasina Role in the China-India-Bangladesh Triangular Relationship - Rahman , Sheikh Aminur (International Journal of Social Sciences and Management, 2025)
Sheikh Hasina's exit has altered Bangladesh's political landscape and its strategic relationships with China and India. The new government is marked by nationalist and Islamist-populist tendencies and prioritizes sovereignty, economic equality, and a variety of international links. This shift has strategic implications: China's economic investments through the Belt and Road Initiative (BRI) remain crucial, while India must contend with bilateral disputes and escalating security worries. The incoming government of Bangladesh is likely to take a balanced stance, striving for economic pragmatism, strategic neutrality, and regional cooperation. This recalibration will alter the balance of power in South Asia, and India will have to adopt a calculated approach to offset China's growing sway. The study examines these shifts and shows how they impact strategic alliances and regional stability. Int. J. Soc. Sc. Manage. Vol. 12, Issue-3: 132-140.